The Phenomenon of School Santrinization in Aceh: Impacts and Implications in Education - Muhammad Riza (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
This article examines the phenomenon of school santrinization in Aceh, Indonesia, and its impacts and implications in the field of education. School santrinization refers to the increasing influence of Islamic boarding school (pesantren) norms, values, and practices within formal educational institutions. This qualitative study employs interviews, observations, and document analysis to explore the impacts of school santrinization and its implications in education. The findings shed light on various changes brought about by school santrinization, including alterations in curriculum content, teaching methods, and student behavior. The analysis reveals that curriculum content has undergone a significant shift, with a heightened emphasis on Islamic studies and a reduced focus on subjects unrelated to religious education. This trend reflects the growing influence of pesantren values in shaping the educational landscape. Furthermore, teaching methods have been influenced, with a greater emphasis on rote memorization and recitation of religious texts, aligning with the pedagogical practices commonly observed in pesantren. These changes in instructional strategies have implications for the overall learning experience of students. Moreover, the study finds that school santrinization has impacted student behavior, leading to a stronger adherence to religious practices and an increased gender segregation within schools. The implications of school santrinization in education are multifaceted. Teachers face challenges in adapting their pedagogical approaches to accommodate the changing educational landscape, striking a balance between religious and secular knowledge domains.